The role of Emiratisation programs in employing beneficiaries of social security in the in the United Arab Emirates society - Al-Raisi, Fatima Khamis; Alothman, Husein (Al-Adab Journal, 2022)
The study aimed to identify the roles of the effectiveness of training Emiratisation programs in employing social security beneficiaries, from the point of view of those who joined the training programs from social security beneficiaries in the UAE society. The study sample consisted of 766 beneficiaries of social security at the level of the United Arab Emirates. In order to achieve the objectives of the study, the researcher used the descriptive approach to analyze the data of the study sample members. The data was analyzed and interpreted and processed statistically using the spss program, by social survey using the study tool questionnaire to obtain quantitative data, while qualitative data was used using a personal interview with a group from officials of the Ministry of Community Development and the Ministry of Human Resources and Emiratisation to collect data. The results of the study showed that there is a statistical significance between the demographic study variables (age, educational level, income, and emirate) on the one hand, and the variable dependent on the study, which is the employment of social security beneficiaries.